Efektifitas Strategi Pengelompokan Gaya Belajar Visual, Auditori, Kinestetik Terhadap Minat Belajar Siswa Pada Mata Pelajaran Ppkn Di Uptd Smpn 2 Burneh Kabupaten Bangkalan - Yuswinardianto, Ferdiyan; Indriani, Dian Eka; Novitasari, Anindita Trinura (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2021)
Learning style is one of the big factors that can influence students' learning interests. In the learning process, students have different learning styles and learning interests. It is only natural that any student with the right learning style will increase the student's learning interest. This research aims to determine the influence between learning styles and students' learning interests partially and simultaneously on the learning homework of PPKn students. The method used is a qualitative descriptive method. The subjects in this study were grade VII students of SMPN 2 Burneh Bangkalan in the 2020 /2021 school year of 21 respondents. The data collection techniques used are questionnaires and interviews. the results showed that SMPN 2 Burneh students had. Most grade VIII students at SMPN 2 Burneh love learning activities by using media related to their learning style, namely media in the form of Visual, Audiotori, and Kinetic. Because it is considered to be more interesting for the student and can further increase the student's learning interest in a subject that the teacher teaches in class. Therefore, media and learning style groupings are very influential in students' learning interests.